Sistem Informasi Akuntansi Pembayaran Spp Pada Sdit Al-Rasyid Islamic School - Nurkholifah, Siti; Karina, Endang; Rengganis, Dewita; Yunita, Yunita (PROFITABILITAS, 2023)
SDIT AL-Rasyid is an educational institution in Karawang Regency which provides basic education with an Islamic approach. This school aims to provide a holistic education, combining academic aspects and Islamic values. The accounting information system for SPP payments at Al-Rasyid Islamic School Integrated Elementary School is a system developed to assist in the management and recording of SPP (Education Development Donations) payments at an Integrated Elementary School (SDIT). This system aims to simplify administration and accounting processes for SPP payments, as well as provide accurate and up-to-date information to interested parties. Currently, the process of paying tuition fees at SDIT is still done manually by using a payment sheet that must be filled in and submitted directly by the parents or guardians of the students to the school. This causes several problems, such as frequent recording errors, late payments, and difficulties in tracking payment history. Therefore, the development of an SPP payment accounting information system is important to increase the efficiency and accuracy of the process. With the existence of an accounting information system for payment of tuition fees at SDIT Al-Rasyid, the administration process for payment of tuition fees becomes more efficient.